2009
DOI: 10.1002/lary.20623
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid septations and their relationship with internal carotid arteries: Anatomical and radiological study

Abstract: As demonstrated both radiographically and endoscopically, most intrasphenoidal septa insert at the parasellar or paraclival carotid prominence. As such, extreme care should be taken when identifying and removing these septations intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 9 publications
7
46
0
3
Order By: Relevance
“…Out of 27 sphenoid sinuses, examined from cadavers, 24 (89%) had one septation inserted in the internal carotid artery. 23 In this current study, Onodi cells were seen in 15 (17.9%) cases. In the paper by Tomovic et al Onodi cells were present in 65.3% of the cases.…”
Section: Discussionsupporting
confidence: 48%
“…Out of 27 sphenoid sinuses, examined from cadavers, 24 (89%) had one septation inserted in the internal carotid artery. 23 In this current study, Onodi cells were seen in 15 (17.9%) cases. In the paper by Tomovic et al Onodi cells were present in 65.3% of the cases.…”
Section: Discussionsupporting
confidence: 48%
“…In this retrospective study with the largest number of cases (n= 314) on this topic in the literature, we examined the parameters that have also reported previously in medical literature such as the degree of sphenoidal pneumatization, number and configuration of the sphenoid septa, the existence and the degree of the sellar bulging (2,5,6,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric studies have shown anatomical landmarks correlating with segments of the ICA . An anatomic and radiographic study by Fernandez‐Miranda et al . showed that intrasphenoidal septations most commonly attach to the ICA canal.…”
Section: Complicationsmentioning
confidence: 99%